Efficacy of acupuncture-related treatment for sleep disturbances in children with neurodevelopmental disorders: a systematic review and meta-analysis - Jeong, Yoon Kyoung; Lee, Sun Haeng (Frontiers in Psychiatry, 2026)
AimTo evaluate the efficacy of acupuncture-related treatments for sleep disturbances in children with neurodevelopmental disorders (NDDs).MethodsA search of 16 databases on May 3, 2025, identified randomized controlled trials on acupuncture-related treatments for this population. The primary outcome was the total score of the Children’s Sleep Habits Questionnaire (CSHQ), with secondary outcomes including CSHQ subscale scores, total effective rate (TER), and polysomnographic parameters. A meta-analysis using R Studio 4.4 included subgroup analyses by acupuncture modality. The risk of bias was evaluated using the Cochrane tool, and the quality of evidence was evaluated.ResultsSeventeen studies involving 1,091 children were included. Acupuncture-related treatment combined with conventional treatment (CT) significantly reduced the CSHQ total scores compared to CT alone (p < 0.0001), with notable improvements in sleep anxiety (p = 0.0023) and nighttime awakenings (p < 0.0001). Improvements were also observed in TER and polysomnographic parameters, such as nighttime sleep time and awakening, with few adverse events. The risk of publication bias was low, and the quality of evidence was rated as moderate for the CSHQ total score and TER.InterpretationAcupuncture-related treatment may be an effective adjunct to nonpharmacological interventions for enhancing sleep disturbances in children with NDDs.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024545366, identifier CRD42024545366.